'I have something to contribute to working life' – students with disabilities showcasing employability while on practical placement. Issue 4 (18th May 2020) - Langørgen, Eli; Magnus, Eva
ABSTRACT: This study explores the practical placement experiences of students with disabilities who are attending professional higher education in Norway. Despite legislative regulations to promote equal opportunities, many students with disabilities face barriers to participation in higher education. In professional education, practical placement is a part of the curriculum. However, the transition from the campus classroom to practical placement puts an extra demand on the students to disclose their disabilities and request accommodation; it also puts demands on academic staff and placement supervisors to arrange support. Based on interviews with 14 students in teacher, social work and healthcare programmes, the study highlights the opportunities that placement gave these students to experiment with the demands of work, learn about their own capacity, and test out solutions for accommodation. Practical placement was also an arena where the students worked hard to develop and demonstrate their resources as proficient future professionals. However, due to structural barriers and insufficient planning, the students risked not being able to cope with the demands of placement and to demonstrate their proficiency. The study revealed that planning prior to placement was essential in providing optimal opportunities for students with disabilities to learn and to market their employability.